2018
DOI: 10.1007/s00262-018-2157-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysate-based vaccines: on the road to immunotherapy for gallbladder cancer

Abstract: Immunotherapy based on checkpoint blockers has proven survival benefits in patients with melanoma and other malignancies. Nevertheless, a significant proportion of treated patients remains refractory, suggesting that in combination with active immunizations, such as cancer vaccines, they could be helpful to improve response rates. During the last decade, we have used dendritic cell (DC) based vaccines where DCs loaded with an allogeneic heat-conditioned melanoma cell lysate were tested in a series of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…The protein concentration was estimated by Bradford's method using a biophotometer (Eppendorf). The human gallbladder cancer lysates (GBCa) (57), human ovarian cancer cell lysates from SKOV3 cell lines (ATCC) (OvCa), leukocyte lysed from PBMC and B16.F10 cell line lysate (B16 lysate) were lysed using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was estimated by Bradford's method using a biophotometer (Eppendorf). The human gallbladder cancer lysates (GBCa) (57), human ovarian cancer cell lysates from SKOV3 cell lines (ATCC) (OvCa), leukocyte lysed from PBMC and B16.F10 cell line lysate (B16 lysate) were lysed using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…These in vitro studies demonstrated that conditioned lysate-matured DCs strongly induced the activation of CD4 + and CD8 + T cells in both allogeneic and autologous cell co-cultures. Moreover, in vitro stimulated CD8 + T cells were able to recognize HLA-matched GBC cell lines, demonstrating efficient priming of DCs by cancer cells and a subsequent presentation of antigens to T cells [134]. These results opened the way for future immunotherapy approaches; however, other studies are needed to characterize immune infiltrates.…”
Section: Molecular Characteristics and Immune Infiltrates In Gbcmentioning
confidence: 89%
“…Importantly, whole tumor lysates can be prepared in several ways, and the methods of inducing cell death, cell stress, or the chemical modification of proteins could impact the immunogenicity and efficacy of the therapy. Current immunogenic treatment modalities used for preconditioning tumor cell lysates include ultraviolet irradiation, oxidation-inducing modalities, and heat shock treatments [29, 32]. We previously showed that the heat shock treatment induces the release of well-established DAMPs, such as CRT and HMGB1, as well as putative DAMPs, such as haptoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of allogeneic heat shock-conditioned tumor cell lysates provides a vast number of different tumor-associated antigens described for melanoma and also delivers different damage-associated molecular patterns (DAMPs) induced by the heat shock, such as high mobility group box-1 (HMGB1) and plasma membrane translocated calreticulin (CRT) necessary for the proper maturation, activation, and cross-presentation of tumor-associated antigens by DCs, enhancing their antitumor-induced responses [2830]. Recently, we have extended our results to other types of tumors, such as prostate cancer and gallbladder cancer, using specific allogeneic heat shock-conditioned cell lysates for each tumor [31, 32].…”
Section: Introductionmentioning
confidence: 99%